2020
DOI: 10.1007/s11469-019-00201-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cannabis Use Disorder Symptoms on Suicidal Ideation in College Students

Abstract: The association of cannabis use and suicidal ideations in adolescents and young adults has been inconsistent. This discrepancy may reflect differences in controlled confounders but also the lack of consideration of the relationships between confounders. In particular, few studies have examined whether controlled variables mediated rather than confounded the relationship between cannabis use and suicide. Participants were 1034 college students who completed questionnaires assessing cannabis use and symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We believe the risks currently outweigh the evidence of temporary symptom relief by cannabis intoxication (Li et al 2020). This is further corroborated by the potential association between cannabis and suicide in individuals with depression (Chabrol et al 2020) or BD (Pinto et al 2019;Bartoli et al 2019).…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 64%
See 1 more Smart Citation
“…We believe the risks currently outweigh the evidence of temporary symptom relief by cannabis intoxication (Li et al 2020). This is further corroborated by the potential association between cannabis and suicide in individuals with depression (Chabrol et al 2020) or BD (Pinto et al 2019;Bartoli et al 2019).…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 64%
“…These studies did not examine whether this link between cannabis use and suicidal behavior was moderated by depressive symptoms. More recently, Chabrol et al (2020) found a dose-response relationship between severity of CUD symptoms and suicidal ideation, which was no longer significant after controlling for depressive symptoms. This suggests that cannabis use may increase the risk of suicidal behaviors through its association with depression.…”
Section: Potential Underlying Mechanismsmentioning
confidence: 99%
“…These findings contrast with an epidemiological study conducted in the UK among young adults, where self-reported use of high- or low-potency cannabis did not correlate with a diagnosis of MDD after controlling for relevant factors, including other substance use ( 61 ). Similarly, Chabrol et al found no significant association between cannabis use disorder (CUD) with suicidal ideation or depressive symptoms in a sample of 1,034 French postsecondary students ( 38 ).…”
Section: Resultsmentioning
confidence: 98%
“…It is the second leading cause of death among youth after road injury [ 4 ], and its prevalence has increased by 30% from 2000 to 2016 in the US [ 3 ]. Suicidality is frequently associated with mental disorders, such as mood disorders, schizophrenia, substance use disorder, anxiety, personality disorders [ 5 , 6 , 7 ], as well as with adverse social and interpersonal conditions [ 5 , 6 , 8 , 9 ], making it a phenomenon that is difficult to predict and to prevent [ 10 ]. Suicide attempts should be seen as the visible consequence of a psychological dynamic rather than like a single self-contained behavior: the suicidal dynamic is sustained by interacting psychological, life history, and social conditions and risk factors [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%